Proceedings of the Twenty-sixth International Congress of Orientalists, New Delhi, 4-10th January - Ghosh, A. K.; Ghosh, A. (1968)
Assistant Editor: H. Sarkar; ersch. 1969; Organising Committee XXVI International Congress of Orientalists; Rs. 40.000; pertinent articles listed suo loco.; Rez.: Or 39 (1970) 205-206 (R. Caplice).